Environmentally Driven Color Variation in the Pearl Oyster Pinctada margaritifera var. cumingii (Linnaeus, 1758) Is Associated With Differential Methylation of CpGs in Pigment- and Biomineralization-Related Genes - Stenger, Pierre-Louis; Ky, Chin-Long; Reisser, Céline M. O.; Cosseau, Céline; Grunau, Christoph; Mege, Mickaël; Planes, Serge; Vidal-Dupiol, Jeremie (Frontiers in Genetics, 2021)
Today, it is common knowledge that environmental factors can change the color of many animals. Studies have shown that the molecular mechanisms underlying such modifications could involve epigenetic factors. Since 2013, the pearl oyster Pinctada margaritifera var. cumingii has become a biological model for questions on color expression and variation in Mollusca. A previous study reported color plasticity in response to water depth variation, specifically a general darkening of the nacre color at greater depth. However, the molecular mechanisms behind this plasticity are still unknown. In this paper, we investigate the possible implication of epigenetic factors controlling shell color variation through a depth variation experiment associated with a DNA methylation study performed at the whole genome level with a constant genetic background. Our results revealed six genes presenting differentially methylated CpGs in response to the environmental change, among which four are linked to pigmentation processes or regulations (GART, ABCC1, MAPKAP1, GRL101), especially those leading to darker phenotypes. Interestingly, the genes perlucin and MGAT1, both involved in the biomineralization process (deposition of aragonite and calcite crystals), also showed differential methylation, suggesting that a possible difference in the physical/spatial organization of the crystals could cause darkening (iridescence or transparency modification of the biomineral). These findings are of great interest for the pearl production industry, since wholly black pearls and their opposite, the palest pearls, command a higher value on several markets. They also open the route of epigenetic improvement as a new means for pearl production improvement.